Transition Metal-Catalyzed Regioselective Direct C–H Amidation: Interplay between Inner- and Outer-Sphere Pathways for Nitrene Cross-Coupling Reactions - Du, Bingnan; Chan, Chun-Ming; Au, Chi-Ming; Yu, Wing-Yiu (Accounts of chemical research, 2022)
Conspectus Catalytic C–N bond cross-coupling reactions have been a subject of fundamental importance in synthetic organic and medicinal chemistry because amides and amines are ubiquitous motifs in natural products, functional materials, and pharmaceuticals. Since the pioneering works of Breslow and Mansuy on the metalloporphyrin-catalyzed direct hydrocarbon amidation using sulfonyliminoiodinane reagents, substantial development has been achieved toward practical and selective amination protocols. Notably, Du Bois’s group developed the dirhodium(II,II) carboxylate catalytic system for direct C(sp3)–H amidations via Rh-sulfonyl nitrene intermediates. Yet, this protocol suffers from competitive alkene aziridination and is limited to electron-rich tertiary and ethereal C–H bonds; analogous direct amidation of arenes remained ineffective. This Account discusses our early effort to explore cyclopalladated complexes for ortho-selective C(aryl)–H amidations. While Buchwald–Hartwig amination cannot be directly applied to arenes, effective amidation of the 2-arylpyridines occurred when an external oxidant such as K2S2O8 was employed. Preliminary studies suggested that the amidation may proceed through reactive Pd-nitrene intermediates. Aiming to develop more diversified amidation protocols, we employed nosyloxycarbamates as nitrene precursors for the Pd-catalyzed ortho-amidation of N-pivalanilides. Likewise, we developed the ortho-selective amidation of benzoic acids to produce anthranilic acids, which are versatile precursors for many medicinally valuable heterocycles. In an attempt to expand the C(aryl)–N coupling reactions to amines, we studied the d6 piano-stool Cp*Rh(III) systems [Cp* = pentamethylcyclopentadienyl]. Our work established a sound reaction platform based on the electrophilic aminating reagents including N-chloroamines, hydroxyamides, and N-carboxyhydrazides for effective C(aryl)–N bond formation in aryl–metal complexes. Building upon the metal-nitrene reaction platform, we moved forward to examine γ-lactam synthesis by intramolecular carbonyl nitrene C(sp3)–H insertion. Noted that carbonyl nitrenes are prone to undergo Curtius-type rearrangement to form isocyanate; we found that the π-basic Ru(II) center effectively decomposes dioxazolones to afford the carbonyl nitrene for regioselective γ-C(sp3)–H insertion. With chiral diphenylethylenediamines (dpen) as ligands bearing electron-withdrawing arylsulfonyl substituents, the [(p-cymene)Ru(dpen)] complex catalyzed the decomposition of the dioxazolones to afford chiral γ-lactams by formal carbonyl nitrene C(sp3)–H insertion. Enantioselective nitrene insertion to allylic and propargylic C(sp3)–H bonds was also achieved with remarkable tolerance to the CC and CC bonds. Notably, the selectivity of the [(p-cymene)Ru] system switched to C(aryl)–H bonds to give dihydroquinolinones when l-proline was employed as ligand. Recently, we aimed to address the regiocontrolled amidation of unactivated methylene C–H bonds using NiH catalyst. While tertiary and benzyl C–H bonds can be differentiated by their bond dissociation energies and steric properties, methylene groups making up the hydrocarbon skeleton display similar electronic and steric properties. In this context, we exploited the five-membered nickelacycle formation to terminate the NiH-mediated chain-walk isomerization, and the nickelacycle reacted with dioxazolones to furnish the C(sp3)–N bond at the γ-methylene position. This Account summarizes our contribution to the development of C–N bond cross-coupling reactions via C–H activation. By exploiting the inner-sphere and outer-sphere reaction pathways, we successfully developed regioselective protocols that target C(sp3)–H and C(aryl)–H bonds. The mechanistic underpinning of the selectivity of different C–H bonds and related studies on the affiliated catalytic systems will be discussed.